Pengaruh Sales Call Anxiety (SCA) pada Kinerja Salespersons Asuransi Jiwa dengan Trait Negative Affectivity (Trait-Na) - Rita, Rita (Bina Nusantara University, 2012)
This study empirically examines the effect of sales call anxiety (SCA) on salesperson performance, good performance in the form of sales volume and sales interactions. This study tested the hypothesis to identify early factors (antecedents) that may affect the sales call anxiety (SCA). Initial factors suspected as the cause of anxiety in sales interactions (SCA) are divided into two conditions, namely canvassing and closing condition. Canvassing consisted of meeting new people, customer with high social status, and being assertive, while the closing is a condition consisting of asking for commitment, and discussing performance with sales manager. The population in this study is all life insurance company salesperson in Palangkaraya. In this study, questionnaires were distributed to 200 people a life insurance salesperson, and then used as a sample is a total of 147 respondents who have a tendency to trait-NA. The sampling method used was purposive sampling. The analysis showed that when the salesperson must meet new customers, customers with a high social status, when they should be able to introduce himself and mission well (canvassing), when they should ask for customer commitments after several meetings and interviews with candidates customers, and when the salesperson must discuss the results of their performance with the sales manager (closing), causing anxiety for the salesperson, because when interacting with potential customers, they have a negative perception of the ability of self, negative perceptions of the mind customers in assessing their work when interacting, the emergence of physiological symptoms, and they take action